Neurologic Events in Continuous-Flow Left Ventricular Assist Devices - Kadakkal, Ajay; Najjar, Samer S (Cardiology clinics, 2018)
Although the growing use of continuous-flow left ventricular assist devices (LVADs) has improved the survival and quality of life of patients with stage D heart failure, ischemic and hemorrhagic cerebrovascular accidents remain one of the most-feared complications of this therapy and a significant source of disability, morbidity, and mortality. In this article, the authors aim to summarize the current data regarding the incidence/prevalence of both ischemic and hemorrhagic stroke in patients with continuous-flow LVADs, compare axial and centrifugal devices, and discuss the major risk factors for neurologic events that have been identified.